2021
DOI: 10.1037/xhp0000929
|View full text |Cite
|
Sign up to set email alerts
|

Lexical stress representation in spoken word recognition.

Abstract: We thank SR Research support specialists Sam Hutton and Kurt Debono for assistance with the eye gaze experiments. This work was supported by the European Union (European Social Fund) and Greek national funds through the operational program "education and lifelong learning" of the National Strategic Reference Framework, research program THALIS-UOA-COGMEK (project 892, MIS 375737). Parts of these data have been presented in the 19 th meeting of the European Society for Cognitive Psychology and the 5 th Panhellen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…However, our results mirror the observations for regular and irregular stress in other studies, such as Burani and Arduino (2004), which found no difference between regular and irregular patterns in Italian in a read-aloud task, and Andrikopoulou et al (2021), which found a priming effect (but no regularity effect) on participants' reaction times for stress patterns in Greek. In line with Andrikopoulou et al (2021), our results suggest that there is no particular representation for regular stress (or default stress, in their terms) in Portuguese. Our observations are also consistent with recent studies that found no processing differences between regular and irregular morphological patterns (see e.g., Nieder et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, our results mirror the observations for regular and irregular stress in other studies, such as Burani and Arduino (2004), which found no difference between regular and irregular patterns in Italian in a read-aloud task, and Andrikopoulou et al (2021), which found a priming effect (but no regularity effect) on participants' reaction times for stress patterns in Greek. In line with Andrikopoulou et al (2021), our results suggest that there is no particular representation for regular stress (or default stress, in their terms) in Portuguese. Our observations are also consistent with recent studies that found no processing differences between regular and irregular morphological patterns (see e.g., Nieder et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…However, examination of another language where stress is variable did not reveal any differences between regular and irregular patterns. Specifically, Andrikopoulou et al (2021) investigated whether regular and irregular stress in Greek (penultimate and antepenultimate, respectively, referred to as dominant and non-dominant by the authors) are retrieved differently in a series of experiments using eye-tracking. With both real and nonce words, participants responded faster to items with matching primes, regardless of stress position, which suggests that lexical representations in Greek are fully specified for stress.…”
Section: Lexical Storagementioning
confidence: 99%
See 1 more Smart Citation